The Association Between Endometriosis Staging and Body Mass Index at Soerya and Putri Maternal and Child Hospitals - Wijaya, Adi Putra; Hendarto, Hendy; Kusumah, Irwin Priyatna (International Journal Labs, 2026)
This study aims to analyze the relationship between endometriosis stages and Body Mass Index (BMI) among women treated at RSIA Soerya and RSIA Putri Surabaya. The research design employed is observational with a cross-sectional approach, involving 52 female patients diagnosed with endometriosis through laparoscopy. Data were collected on demographic characteristics, BMI, and endometriosis stages based on the rASRM classification. The results indicate that the majority of respondents fell into the normal to overweight BMI categories, with a predominance of stage IV endometriosis in this population. Chi-Square testing revealed no significant relationship between BMI and endometriosis stage, with a p-value of 0.298. This indicates that BMI status does not serve as a reliable indicator for assessing the severity of endometriosis stages.